Francisco Campos e a construção do autoritarismo brasileiro: educação, democracia e sociedade - Rio, Josué Justino do (Universidade Federal de São Carlos, 2020)
The aim of the research is to understand the conservative thinking of Francisco Campos and his reflections in Brazilian politics, especially during the Estado Novo, in the measure that he was the idealizer, based on the ideological construction of the National State. The research is justified by being an intellectual sometimes forgotten, but who played a prominent role in the national politics of his time, because camper thinking was based on integralist ideas and the European authoritarian and totalitarian movements of the early nineteenth century, and which were consolidated in Italian fascism, german nazism and bolshevik totalitarianism. The study is also relevant because Francisco Campos is characterized as anti-liberal and critical of party democracy, since in his perspective, this political model did not meet the new demands of the masses. In order to understand the camper thought, then, an investigation was needed in the period 1891-1968, passing through the brazilian integralist movement, led by Plínio Salgado, who contributed to the construction of Francisco Campos' conservative thinking due to the fascist influence. In addition, in order to reach the specific goal, that is, to identify whether Francisco Campos can be considered an authoritarian or totalitarian intellectual, it was essential to carry out an investigation of convergent points of thought campers with the political theology of Carl Schmitt, confronting them with the categories totalitarian views presented by Hannah Arendt. We also take advantage of Giorgio Agamben, especially his state of exception. The problem with the investigation lies in the fact that Brazil has always been lacking in its own political thinking, so much so that Francisco Campos, seeking to construct original thinking, flirted with authoritarian regimes and European totalitarian theories. However, to what extent did this contact with anti-liberal ideologies converge in the formation of his conservative thinking. In short, it takes care of a bibliographic and documentary research, since the proposal required an analysis of the works and writings to understand the formation of camper thinking, as well as the influence suffered by the Schmittian and integralist theories. In this complex scenario, it can be concluded that Francisco Campos, although conservative authoritarian thinking and advocate of dictatorship as a form of consolidation of a nationalist government, in opposition to liberal ideas, cannot be accused of totalitarianism, even if both Francisco Campos and Carl Schmitt are contemporary and some points of their theories may even converge.
Francisco Campos and the construction of brazilian authoritarianism: education, democracy and society
Keywords: Autoritarismo; Totalitarismo; Educação; Democracia; Sociedade; Authoritarianism; Totalitarianism; Education; Democracy; Society; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO